2016
DOI: 10.1007/s13762-016-1229-3
|View full text |Cite
|
Sign up to set email alerts
|

Batch and continuous removal of heavy metals from industrial effluents using microbial consortia

Abstract: Bio-removal of heavy metals, using microbial biomass, increasingly attracting scientific attention due to their significant role in purification of different types of wastewaters making it reusable. Heavy metals were reported to have a significant hazardous effect on human health, and while the conventional methods of removal were found to be insufficient; microbial biosorption was found to be the most suitable alternative. In this work, an immobilized microbial consortium was generated using Statistical Desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…Jha et al (2014) found that Cu(II) uptake by using Aspergillus lentulus biomass from industrial effluents collected from two sources was efficient. Migahed et al (2017) succeeded in removing all the chromium ions and more than half of the iron ions from both the prepared standard solutions and the real industrial effluents even in the presence of other heavy metals by using a mixture of fungal spores and bacterial biomass in batch and continuous modes to remove lead and chromium ions from the industrial effluents of four different factories.…”
Section: Discussionmentioning
confidence: 99%
“…Jha et al (2014) found that Cu(II) uptake by using Aspergillus lentulus biomass from industrial effluents collected from two sources was efficient. Migahed et al (2017) succeeded in removing all the chromium ions and more than half of the iron ions from both the prepared standard solutions and the real industrial effluents even in the presence of other heavy metals by using a mixture of fungal spores and bacterial biomass in batch and continuous modes to remove lead and chromium ions from the industrial effluents of four different factories.…”
Section: Discussionmentioning
confidence: 99%
“…The used cells achieved a 100% removal of Ni 2+ , Cr 2+ , Cd 2+ and Pb 2+ ions, indicating the successful ability of L. plantarum MF042018 to remove a mixture of heavy metals from the industrial effluent within 1 hr only. Furthermore, applying the microbial mass hanged in a dialysis tube is considered a significant criterion, to facilitate the collection and separation of cells from the treated industrial effluent for further use 41 .…”
Section: Removal Of Heavy Metals From Battery-manufacturing Effluent mentioning
confidence: 99%
“…The biosorption of metal ions by B. subtilis has been studied (Al-Gheethi et al 2017;Cai et al 2018). Besides, many studies reported the biosorption of iron by various microbial biosorbents (Keshtkar et al 2016;Migahed et al 2017). However, there is very little information regarding the structural and functional changes occurring on the biomass of B. subtilis as a consequence of iron biosorption.…”
mentioning
confidence: 99%